Isolation and characterization of nickel, lead, copper, and cadmium-multiresistant bacteria from the Citarum River, West Java - Deokward F. Ruga; Wahyu Irawati (Jurnal Biologi Papua, 2026)
Industrial activities along the Citarum River, West Java, have resulted in serious heavy metal contamination, causing negative impacts on aquatic ecosystems and human health. Bioremediation using indigenous bacteria with multi-metal resistance offers an efficient and environmentally friendly solution because these bacteria are directly obtained from contaminated environments and are resistant to several heavy metals simultaneously. This study aimed to isolate and characterize indigenous bacteria from the Citarum River that are multiresistant to a mixture of four heavy metals, namely nickel, lead, copper, and cadmium. The bacteria were isolated using the spread plate method on Luria–Bertani Agar supplemented with a mixture of those heavy metals at a concentration of 1 mM. The isolates were purified by the streak plate method and characterized based on colony morphology and cell morphology through Gram staining. The results showed that 24 bacterial isolates were successfully obtained, all of which were able to grow in a 1 mM mixture of nickel, lead, copper, and cadmium. Morphological characterization revealed diverse colonies dominated by yellow, white, and brown pigmentation, with circular shapes and smooth margins. Gram staining showed that all isolates were Gram-negative bacteria. A total of 16 isolates exhibited darker pigmentation, ranging from dark brown to blackish, when cultivated on heavy-metal-containing media. Dark-colored colonies indicate intensive interactions through biosorption and bioprecipitation mechanisms, resulting in the formation of insoluble compounds such as metal sulfides on the cell surface.